Liberal Radicalism: A Flexible Design For Philanthropic Matching Funds - Buterin, Vitalik; Hitzig, Zoe; Weyl, E. Glen (SSRN, 2018)
We propose a design for philanthropic or publicly-funded seeding to allow (near) optimal provision of a decentralized, self-organizing ecosystem of public goods. The concept extends ideas from Quadratic Voting to a funding mechanism for endogenous community formation. Citizens make public goods contributions to projects of value to them. The amount received by the project is (proportional to) the square of the sum of the square roots of contributions received. Under the "standard model" this yields first best public goods provision. Variations can limit the cost, help protect against collusion and aid coordination. We discuss applications to campaign finance, open source software ecosystems, news media finance and urban public projects. More broadly, we relate our mechanism to political theory, discussing how this solution to the public goods problem may furnish neutral and non-authoritarian rules for society that nonetheless support collective organization.